Shareholder’s reaction to Merger and acquisition announcement: evidence from india’s Manufacturing sector - I. Gupta; T. V. Raman (Финансы: теория и практика, 2022)
Mergers and acquisitions performance is akin to financial perplex that researchers have been trying to solve. The objective of the study is to examine the reaction of shareholders to the announcement of mergers and acquisitions in the pre-event, around the event and during the post-event period of the Indian manufacturing firms. The event study research methodology has been used for analysis along with parametric and non-parametric tests. The study shows that investors can earn a significant return if they purchase shares of the acquiring company one day before and sell them one day after the announcement day. The findings concluded that while the announcement of a merger or acquisition generates a positive reaction, this reaction is only temporary and is swiftly diluted. This shows that investors initially overreacted to these announcements and took immediate corrective action. The study recommends to investors, “Earlier the shareholders sell, more the shareholders gains”.